Personal strivings, spirituality and academic achievement - Costa, Liza C. (2006)
This study was conducted to identify the motivational mechanism of personal strivings that can predict the academic achievements of students and educational qualifications of faculty members. Participants included 120 college students and 30 faculty members of the Cavite State University. This descriptive-correlational study used the Two-group Randomized Multiple Observation Design. Findings revealed that students' personal striving system was dominated by extrinsic and materialistic striving influences. Faculty members' personal striving system was dominated by spiritual, intimacy, achievements, personal growth and health, affiliation and independence.
"April 2006."
Thesis (Ph.D. Educational Psychology)--University of the Philippines, Diliman.
Keywords: Universities and colleges -- Philippines -- Cavite; Academic achievement -- Philippines -- Cavite; Goal (Pschology)